Tropidia scita (Harris, 1780) (Diptera: Syrphidae), a new hoverfly species for Slovenia - Benjamin Schwartz; Maarten de Groot (Natura Sloveniae)
The hoverfly genus Tropidia Meigen, 1822, with the species T. scita (Harris, 1780), is recorded for the first time in the hoverfly fauna of Slovenia. This species was found at Draga ponds near Ig, Slovenia, on the 16th of June, 2024. With this new record, the number of hoverfly species in Slovenia has increased to 363.